South-South cooperation - Muhr, T. (Elgar encyclopedia of development, 2023)
This entry reviews South-South cooperation (SSC) as a contested concept and social practice. A periodisation of SSC post-1945, derived from historical turning points, provides an analytical framework specifically for identifying conceptual shifts in the global context: Concertation (1945–1981); Containment (1981–1995); and Cooptation vs Confrontation (1995–present). On this basis, major controversies are explored.